Migration and human rights : the United Nations Convention on Migrant Workers' Rights - Cholewinski, Ryszard (UNESCO Pub. ParisFR, 2009)
Provides in-depth information on the Convention. Highlights the opportunities and challenges it presents for states to develop new policies on migration and the treatment of migrants. Explores the reasons behind many states' reluctance towards its ratification.